Pengaruh Pemberian Jus Buah Naga (Hylocereus Polyrhizus) dan Madu Dengan Kombinasi Tablet Fe Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Dengan Anemia - Vitria Meilinda; Alitta Dwi Namira Natasya (Universitas Fort de Kock Bukittinggi, 2023)
According to the World Health Organization (WHO), 40% of pregnant women worldwide suffer from anemia. Anemia in pregnancy is a condition in which pregnant women have Hb levels < 11.00 g% in the I, II and III trimesters or Hb levels < 10.50 g% in the second trimester, because there are differences in hemodilution, especially in the second trimester. Efforts to overcome iron deficiency anemia in pregnant women can be done medically and non-medically (complementary). The purpose of this study was to determine the effect of dragon fruit juice (Hylocereus Polyrhizus) and forest honey combine with Fe tablets to increase Hb levels in pregnant women with anemia in the Working Area of Harapan Raya Community Health Center Pekanbaru in 2022. The type of this study was a Quasy Experiment, with a design a one-group pretest-posttest study, namely by conducting a pre-test study of Hemoglobin levels in research subjects and then giving treatment to research subjects, after that a post-test assessment of Hemoglobin levels was carried out on the research subjects. The results showed that the average Hb level of pregnant women before being given dragon fruit was 10,558 (SD .2107) and after being given dragon fruit, the average Hb level of pregnant women was 11,776 (SD .2716). Based on the results of statistical tests, it was found that there was an effect of giving dragon fruit to increase hemoglobin levels in pregnant women (p = 0.000 (<0.05)). The conclusion of this study is dragon fruit juice and honey have an effect in increasing Hb levels in pregnant women with anemia. It is recommended to Harapan Raya Community Health Center Pekanbaru to provide education to pregnant women that Dragon Fruit can be used as an alternative to Fe tablets to increase hemoglobin levels in pregnant women.